Design and selective photocatalytic activity of highly concentrated C, N, O co-doped Zn, S co-defective ZnS particles mediated by ethylenediamine derivatives. (April 2023) - Moon, Hojun; Kim, Sujeong; Joo, Sang Woo; Kim, Minkyu; Park, No-Kuk; Baek, Jeom-In; Ryu, Ho-Jung; Kim, Joonwoo; Son, Namgyu; Kang, Misook
Abstract: ZnS particles are synthesized by adding ethylenediamine ( en ) and its derivatives, triethylenetetramine ( trien ) and ethylenediaminetetraacetate (EDTA), as capping agents. In the capped ZnS particles, Zn and S defects due to O, N-doping and loading of carbon dots (CDs) are confirmed. The degree of defects is suggested from photoluminescence (PL) spectra and density of states calculations. The intensities of PL are lowered in the order of ZnS-none> ZnS-EDTA> ZnS-en> ZnS-trien, while the photocurrent densities are increased in the opposite order. Time resolved PL shows extremely slow recombination of photo-excited charges in ZnS-trien. ZnS-trien is the most suitable for catalyzing CO2 reduction, and ZnS-en is the best for water-splitting. The excellent photocatalytic activity of ZnS-trien encapsulated with N-CDs shell maintains without photo-corrosion over more than five recycling experiments. Eventually, this study reveals that well-ordered ZnS with C, N, O co-doping-induced Zn, S co-defects is self-assembled using en -derivatives as capping agents, exhibits good photocatalytic activity without grafting with other particles. Graphical Abstract: ga1 Highlights: Highly concentrated C, N, O co-doped Zn, S co-defective ZnS particles mediated by ethylenediamine derivatives. ZnS-trien was suitable for CO2 reduction and ZnS-en for water splitting, respectively. ZnS-trien encapsulated in CD shell was stable without photocorrosion in more than five recycling experiments.